Augmented reality navigation technology in atlantoaxial pedicle screw fixation for atlantoaxial dislocation treatment - Zhang, Peihai; Sun, Zhenxing; Zhang, Kai; Guo, Jiahe; Yang, Xuejun (Frontiers in Surgery, 2025)
ObjectiveThis study aims to evaluate the clinical safety and feasibility of augmented reality (AR) navigation technology in atlantoaxial pedicle screw placement.MethodsFrom May 2024 to December 2024, 20 patients with atlantoaxial dislocation undergoing internal fixation were enrolled. During surgery, a real-time CT scan was obtained using an O-arm imaging system, which was processed by the navigation workstation to generate AR images. These AR images can be overlaid directly onto the surgeon's field of view, guiding him to complete pedicle screw placement. The clinical feasibility and safety were evaluated based on operative time, user experience, and the Gertzbein-Robbins scale.ResultsAll 20 patients successfully underwent surgery, with a total of 80 pedicle screws placement All screws met clinical safety standards, and no severe complications were observed. The operative time ranged from 16 to 21 min, with an average implantation time of 104 s per screw. The average user experience score was 90.5 points.ConclusionThis study preliminarily validates the clinical value of AR navigation technology in atlantoaxial pedicle screw fixation, supporting further investigation.